1985
DOI: 10.1002/hlca.19850680114
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Octa‐ and Decapeptides as Ionophores for Magnesium

Abstract: Cyclic octa-and decapeptides have been prepared, and their ion selectivity in solvent polymeric membranes was studied. Cyclo(-LPro-DLeu-)5 behaves as an ionophore which selects Mg2+ over CaZ+ by a factor of 100.Cyclo(LPro-LLeu), induces selectivity in membranes for Mg2+ over Li+, Na+ and K' by a factor of 400,200 and 10, respectively, while selectivity of Mg2+ over Ca2+ is poor. Some evidence is presented which indicates that certain ionophores exhibit high selectivity for monovalent magnesium complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The influence of the concentration of KTpClPB (0-100 mol %) on the properties of the membranes was also investigated. It was found that in the absence of KTpCIPB, ionophores 1 and 7 show no activity in the membrane The fact that certain ligands behave as carriers only if lipophilic anionic sites are simultaneously present in the membrane phase has been observed earlier [9]. Also, the presence of KTpClPB exerts a decisive effect on the electrode response ( Figure 5).…”
Section: Results and Drscussroivmentioning
confidence: 64%
“…The influence of the concentration of KTpClPB (0-100 mol %) on the properties of the membranes was also investigated. It was found that in the absence of KTpCIPB, ionophores 1 and 7 show no activity in the membrane The fact that certain ligands behave as carriers only if lipophilic anionic sites are simultaneously present in the membrane phase has been observed earlier [9]. Also, the presence of KTpClPB exerts a decisive effect on the electrode response ( Figure 5).…”
Section: Results and Drscussroivmentioning
confidence: 64%
“…Alternatively, with cyclo(LPro-DLeu-), (Figure l(4)) and cyclo(LPro-DLeu-LPro-LLeu-LPro-Leu-DPro-LLeu-LPro-Leu-), the logarithmic selectivity coefficient over calcium ions was <-2 while the required selectivity over monovalent ions was lost (Behm et al: cyclic octa-and decapeptides as ionophores for magnesium) [16]. The influence of the concentration of anionic sites (KTpClPB, potassium-tetrakis-(4-~hlorophenyl)-borate) within the membrane on the selectivity scale of these carriers was tested.…”
Section: The Period Of Antibiotics and Peptidesmentioning
confidence: 99%
“…I401 and the measurements of Simon and coworkers [41] with peptides for ion-selective membranes). We also plan to investigate the possible transport of ions through liposomes by these compounds.…”
Section: )mentioning
confidence: 95%